Innovation of regional language learning media based on gamification for the revitalization of the Batak Toba language - M. Deny Effendy Tambusay (TALENTA, 2025)
The preservation of regional languages is crucial in maintaining national cultural identity. According to data from the Language Development and Cultivation Agency, in 2023, there will be 718 languages in Indonesia spread across 2,560 observation areas, with 11 declared extinct. One of the causes of language extinction is the apathy of speakers towards their language, especially among the younger generation, who tend to use slang. Opisada was developed as a regional language learning media based on gamification to support the revitalization of the Batak Toba language. In the initial trial phase, Opisada was implemented at SDN 173525 Balige, Toba Regency, North Sumatra, as part of language activities by the Language Ambassadors of North Sumatra in 2023. This study assesses whether Opisada can enhance the interest, knowledge, and skills in speaking Batak Toba through a game-based learning approach that integrates local cultural wisdom. The methods applied in this study include three main stages: preparation (needs analysis, material validation, instructional design), implementation (socialization, games, and mentoring), and evaluation (pre-test and post-test). A total of 20 students participated in this study. Learning scores were measured using the N-gain score, representing the standardized difference between the pre-test and post-test results. The average pre-test score increased from 4.05 to 13.35 in the post-test, with an average N-gain of 0.592, indicating a moderate improvement in Batak Toba language proficiency. Data analysis using IBM SPSS Statistics 26 showed a significant improvement in Batak Toba language mastery. These findings suggest that Opisada is effective as an interactive and educational learning media, which has the potential to be developed as a prototype for regional language learning media in Indonesia to support the strengthening and revitalization of regional languages.